Meta-Analysis: Intervention Using Midfulness Training to Reduce Burnout in Medical Doctors - Ratri, Maika; Murti, Bhisma; Tamtomo, Didik Gunawan (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2022)
Background: Burnout is one of the mental health problems caused by a high workload that causes excessive stress characterized by symptoms such as anxiety and even depression, because of the seriousness of this burnout problem, the WHO classifies burnout as a disease. Burnout is a very serious problem in many countries, so efforts are needed to prevent and/or reduce the negative consequences and impacts of burnout syndrome. One of the interventions that can be done to achieve this is using the mindfulness method. This study aims to examine the effectiveness of mindfulness in reducing burnout levels in doctors.Subjects and Method: This meta-analysis study was conducted using PICO as follows: The population is doctors (general and specialist) who work in hospitals. Intervention is mindfulness. Comparison in the form of mindfulness therapy. The outcome is a low level of burnout. Sources of meta-analysis studies were accessed using: Clinical Key, Google Scholar, MEDLINE/PubMed, Science Direct. The articles used in this study are full-text articles with a Randomized Controlled Trial (RCT) study design. This meta-analysis used 10 articles with a total sample of 539 doctors who were divided into two groups (mindfulness group and no mindfulness group). Analysis of the data using the application Review Manager 5.4.1. The purpose of this study was to determine the Standardized Mean difference (SMD) and heterogeneity in the study sample.Results: The results showed that this study was homogeneous (I2=47%; P<0.001) so the Fixed Effect Model (FEM) was used. Mindfulness intervention was effective in reducing burnout levels in doctors 0.20 units lower than without using mindfulness and the results were statistically significant (SMD -0.20; 95% CI -0.37 to -0.03; p=0.020).Conclusion: Mindfulness is effective in reducing burnout levels in doctors 0.20 units lower than without using mindfulness and the results are statistically significant. Keywords: mindfulness, burnout, doctor.Correspondence: Maika Ratri. Masters Program in Public Health, Universitas Sebelas Maret. Jl. Ir. Sutami 36A, Surakarta, Central Java. Email: ratrim.mr@gmail.com.Mobile: +6285702081870.Journal of Health Policy and Management (2022), 07(01): 24-33https://doi.org/10.26911/thejhpm.2022.07.01.03